Ultracompact Surface Plasmon Polariton Unidirectional Generator Based on Asymmetric Single-Nanoslit - Li, Zhi; Chen, Jianjun; Yue, Song; Qihuang Gong (2011 CONFERENCE ON LASERS AND ELECTRO-OPTICS (CLEO), 2011)
An asymmetric single-nanoslit with lateral dimension of only 370 nm is demonstrated to work as an efficient SPP unidirectional generator at wavelength of 830 nm.